Literasi Digital Lansia: (Studi Fenomenologi Pemanfaatan Aplikasi WhatsApp Pada Lansia Indonesia Ramah Lansia Kota Bandung) - Adiva Vanka Tamika; Rini Rinawati (Bandung Conference Series: Public Relations, 2023)
Abstract. Cannot be denied that the elderly population is the most vulnerable group when it comes to the use of digital technology. The lack of understanding and education among the elderly makes them highly susceptible to spreading hoaxes or becoming victims of digital scams. Digital literacy is considered crucial in order to prevent these negative impacts. The purpose of this study is to determine the utilization of WhatsApp applications among the elderly who are part of the Elderly-Friendly Indonesia initiative in Bandung City. This research utilizes a qualitative research method through a phenomenological approach and employs a constructivist paradigm. The informants in this study consist of three elderly individuals who are members of the Elderly-Friendly Indonesia initiative in Bandung City. The study incorporates theories of New Media, Social Construction, and Phenomenology. The data for this research is obtained through semi-structured interviews with the three informants. Additionally, data from the research results are also gathered through participant observation. The findings of this study reveal several motives of the elderly in using the WhatsApp application, including recommendations from their children, accidental discovery, keeping up with technological advancements, easy access to information flow, and of course, the motives are aimed at facilitating communication. The study also uncovers the experiences of the elderly in using the WhatsApp application, such as positive experiences, negative experiences, the use of free voice and video calls as the main features, and regular usage frequency. Based on the experiences they have had, the elderly perceive hoaxes as false news and recognize their negative impacts. Furthermore, several factors that hinder the fulfillment of digital literacy among the elderly are identified, including dependence on others, limitations in verification, declining memory capacity, and limited understanding of digital literacy-related issues. Abstrak. Tidak dapat dipungkiri bahwa kelompok masyarakat lansia merupakan khalayak yang paling rentan pada penggunaan teknologi digital. Pemahaman dan edukasi yang kurang terhadap para lansia menyebabkan lansia merupakan rentan usia paling banyak menyebarkan hoaks maupun menjadi korban penipuan digital. Literasi digital dianggap penting sekali dilakukan kepada para lansia untuk mencegah dampak-dampak negatif tersebut. Tujuan penelitian ini adalah untuk mengetahui pemanfaatan aplikasi WhatsApp pada lansia yang tergabung dalam Indonesia Ramah Lansia Kota Bandung. Penelitian ini menggunakan metode penelitian kualitatif melalui pendekatan fenomenologi dan dengan menggunakan paradigma konstruktivis. Informan pada penelitian ini merupakan 3 orang lansia dari standar 3 Indonesia Ramah Lansia Kota Bandung. Penelitian ini menggunakan Teori Media Baru, Konstruksi Sosial dan Fenomenologi. Data-data dalam penelitian ini diperoleh melalui wawancara semi terstruktur dengan ketiga informan. Selain itu, data hasil penelitian juga diperoleh melalu observasi partisipasi. Hasil dari penelitian ini diperoleh sebuah motif lansia dalam menggunakan aplikasi WhatsApp yaitu rekomendasi anak, fasilitas, mengikuti perkembangan teknologi, kemudahan arus informasi dan tentunya motif-motif tersebut bertujuan untuk kemudahan komunikasi. Ditemukan pula pengalaman lansia dalam menggunakan aplikasi WhatsApp yaitu pengalaman positif, penglaman negatif, penggunaan free call dan video call sebagai fitur utama, dan frekuensi penggunaan rutin. Dari pengalaman yang lansia rasakan kemudian lansia memaknai hoaks sebagai berita tidak benar dan hoaks berdampak negatif. Selanjutnya ditemukan beberapa faktor penghambat pemenuhan literasi digital lansia yaitu ketergantungan terhadap orang lain, keterbatasan verifikasi, kemampuan daya ingat menurun dan keterbatasan pemahaman terkait literasi digital